Reflexin A, a new indole alkaloid from Rauvolfia reflexa induces apoptosis against colon cancer cells - Fadaeinasab M.; Karimian H.; Omar H.; Taha H.; khorasani A.; Banisalam B.; Aziz Ketuly K.; Abdullah Z. (Taylor and Francis Ltd., 2023)
antineoplastic agent; caspase 3; caspase 7; caspase 8; caspase 9; indole alkaloid; macusine; Rauvolfia reflexa extract; Rauwolfia extract; reflexin A; unclassified drug; vinorine; flavanone derivative; indole alkaloid; reflexin; acute toxicity; antineoplastic activity; apoptosis; Article; bark; cell invasion; cell migration; cell proliferation; colon cancer; controlled study; drug isolation; drug safety; drug structure; enzyme activation; G1 phase cell cycle checkpoint; HCT 116 cell line; human; human cell; IC50; Rauvolfia reflexa; Rauwolfia; apoptosis; chemical structure; colon tumor; Apoptosis; Colonic Neoplasms; Flavanones; Humans; Indole Alkaloids; Molecular Structure; Rauwolfia